Comparative Metagenomic Analysis of Two Hot Springs From Ourense (Northwestern Spain) and Others Worldwide - DeCastro, María-Eugenia; Escuder-Rodríguez, Juan-José; Becerra, Manuel; Rodríguez-Belmonte, Esther; González-Siso, María-Isabel (Frontiers in Microbiology, 2021)
With their circumneutral pH and their moderate temperature (66 and 68°C, respectively), As Burgas and Muiño da Veiga are two important human-use hot springs, previously studied with traditional culture methods, but never explored with a metagenomic approach. In the present study, we have performed metagenomic sequence-based analyses to compare the taxonomic composition and functional potential of these hot springs. Proteobacteria, Deinococcus-Thermus, Firmicutes, Nitrospirae, and Aquificae are the dominant phyla in both geothermal springs, but there is a significant difference in the abundance of these phyla between As Burgas and Muiño da Veiga. Phylum Proteobacteria dominates As Burgas ecosystem while Aquificae is the most abundant phylum in Muiño da Veiga. Taxonomic and functional analyses reveal that the variability in water geochemistry might be shaping the differences in the microbial communities inhabiting these geothermal springs. The content in organic compounds of As Burgas water promotes the presence of heterotrophic populations of the genera Acidovorax and Thermus, whereas the sulfate-rich water of Muiño da Veiga favors the co-dominance of genera Sulfurihydrogenibium and Thermodesulfovibrio. Differences in ammonia concentration exert a selective pressure toward the growth of nitrogen-fixing bacteria such as Thermodesulfovibrio in Muiño da Veiga. Temperature and pH are two important factors shaping hot springs microbial communities as was determined by comparative analysis with other thermal springs.